Artificial light at night impacts night-time activity but not day-time behaviour in a diurnal coral reef fish - Georgiou, Demi; Reeves, Simon E.; Burke da Silva, Karen; Fobert, Emily K. (Basic and applied ecology, 2024)
An important, yet overlooked form of anthropogenic pollution is sensory pollution, and one of the most pervasive forms of sensory pollution is artificial light at night (ALAN). Despite the growing use of ALAN across the globe, limited research has examined the impacts of ALAN on coral reef fish. This study aims to further our understanding of the behavioural impacts of light pollution on fish by exposing the humbug damselfish (Dascyllus aruanus) to ALAN (∼15-25 lux, white LED light) over a period of 14 days, in situ. We assessed nocturnal activity, and diurnal shelter use and emergence time following a simulated threat in natural (control) and ALAN conditions. D. aruanus colonies exposed to ALAN were active at night and were lacking cryptic colouration observed in control fish, however this altered nocturnal activity did not appear to impact the diurnal behaviours we measured. Our findings provide critical insight into the impact of ALAN exposure to nocturnal behaviour of a diurnal fish and highlight the potential for increased risk of nocturnal predation under ALAN. Further studies with a longer ALAN exposure time will help illuminate the extent of behavioural changes and implications caused by ALAN in shallow coral reef systems.